STUDI PEMANFAATAN TUMBUHAN FAMILIA ZINGIBERACEAE YANG BERKHASIAT OBAT DI KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Fernando, Oki - (STKIP PGRI Sumbar, 2014)
Ethnobotany is the study of plants used by peoples with traditionally. In the life are fivecategories plant benefit, one of wich used as medicine. One of the groups of plants are used formedicinal is plants from family Zingiberaceae that contains many active compounds includingflavonoids, saponins and essential oils. In Indonesia, the used of plants for treatment are stilldeveloping in the peoples, as in district of Luhak Nan Duo peoples in West Pasaman. Thisresearch has been conducted in March 2014. The method that as use is descriptive survey methodusing observation and interview techniques. The selection of the respondents using purposivesampling technique. The research meet 6 species of medicinal plant from family Zingiberaceaeas Alpinia galangal, Costus speciosa, Curcuma domestica, Curcuma xanthoriza, Zingiberofficinale and Zingiber purpureum. The medicinal plant can treat eleveen kinds of diseases. Fivekind of diseases can be treat with a single drug and six kind of diseases can be treat withmedicinal herbs.